[[125I]]Azidonicotinoid photoaffinity labeling of insecticide-binding subunit of Drosophila nicotinic acetylcholine receptor. - Tomizawa, M.; Casida, J.E. (Neuroscience Letters, 1997)
The novel synthetic nicotinoid insecticide imidacloprid is a high affinity ligand for the insect nicotinic acetylcholine receptor (nAChR). The goal of this study is to identify the ligand- and insecticide-binding subunit of Drosophila nAChR with a novel [125I]azidonicotinoid ([125I]AN) photoaffinity probe modeled on imidacloprid. [125I]AN photoaffinity labels a single polypeptide in Drosophila head membranes corresponding in molecular mass to 66 kDa at a specific site inhibited by various cholinergic ligands including (-)-nicotine, cytisine, carbachol, alpha-bungarotoxin and d-tubocurarine as well as the insecticides imidacloprid and acetamiprid, pharmacologically consistent with the ligand- and insecticide-binding subunit. The Drosophila nAChR, isolated with three putative subunits (69, 66 and 61 kDa) using a nicotinoid-agarose affinity column, is labeled by [125I]AN primarily at the 66 kDa subunit and secondarily at the 61 kDa subunit. Clearly, the novel synthetic nicotinoid insecticides are valuable contributors in exploring the structure and function of the Drosophila nAChR.